The new iron(III) 3‐oxo‐N‐(pyridin‐2‐yl)butanamide complex promotes Ehrlich solid tumor regression in mice via induction of apoptosis. (13th November 2019) - Saad, Entsar A.; Elsayed, Shadia A.; Hassanien, Mohamed M.; AL‐Adl, Menna S.
Abstract : Currently used chemotherapeutic drugs had serious adverse effects e.g. myelo‐suppression, anemia and nephrotoxicity. Thus, developing new alternatives is of great importance. We aimed to develop a new prospective antitumor complex combines iron metal ion and 3‐oxo‐N‐(pyridin‐2‐yl)butanamide ligand that may be effective with less toxicity towards healthy tissues. Anticancer activities of the developed complex were studied in vitro and in vivo using induced Ehrlich solid tumor in mice as animal model. In vitro, the complex (1 mmol/L) exhibited superoxide dismutase (SOD)‐like activity of 86.69 %, catalase‐like activity of 170 U/100 mL, and 99.06% mortality of Ehrlich ascites carcinoma (EAC) cells. Complex ability to interact with DNA was proved spectrophotometrically. Flow‐cytometrically, EAC cells treated with the complex showed higher apoptosis, caspase 3 activity, and p53 compared to the untreated EAC cells. In vivo, the complex showed prominent dose‐dependent antitumor activities. It reduced tumor volume and weight, prolonged mice life span, and reversed the hematological indices, malondialdehyde (MDA), total antioxidant capacity (TAC), ALT and urea levels towards normal. Finally, our findings indicate that the complex motivates Ehrlich solid tumor regression in mice via induction of apoptosis. Its effect was better than that of cisplatin. Abstract : After monitoring for 180 days of tumorized mice treated with the complex (0.214 mg/kg), no any visible tumor was seen.